The interaction of population growth and environmental quality. - Cropper, Maureen; Griffiths, Charles (American Economic Review, 1994)
An important question for policy is whether holding constant per capita income and other relevant factors population pressures have a significant effect upon environmental degradation. The authors examine the effect of population pressures upon deforestation in 64 developing countries in an attempt to provide relevant empirical findings. Data on deforestation were drawn from the Food and Agriculture Organizations Production Yearbook. Results suggest that a relationship exists between per capita income and deforestation and that for Africa rural population density shifts the relationship upward. The increase in the rate of deforestation levels off as income increases. The rate of growth in per capita income also has a significant negative impact upon deforestation although the magnitude of the effect is small. The authors close in stressing that reducing the rate of population growth is not necessarily the best way to reduce the rate of deforestation. Deforestation in developing countries is really a problem of market failure. Since property rights are often neither defined nor enforced there is essentially no private cost of deforestation. With no long-term stake in the land people have no incentive to use land efficiently. This situation must be addressed in conjunction with the problems of poverty and population growth.